The zooming-speed illusion: A meta illusion? - Ashida, Hiroshi; Kitaoka, Akiyoshi (i-Perception (London), 2023)
A movie taken from the front window of a running train, with zooming in and out, has been popularly acknowledged as a perceptual illusion such that the train motion is perceived as much slower when zoomed in. This is, however, not a real illusion because the image speed varies as a function of the focal length of the lens. This could be a meta-illusion, that is, an illusory sense of illusion, that might reflect a lack of understanding of how zooming changes the geometrical structure of the image.